Percepção de docentes e discentes acerca da avaliação da aprendizagem: estudo de caso em escola pública de ensino médio e profissionalizante - Rocha, Maria Luciene Feitosa (2005)
This study has aim to characterize and interpret the meaning of the apprenticeship -aluation for teaching and learning staff at Amilcar Ferreira Sobral School CAFS),technic and intermediate teaching schoollocated in Floriano -PI. Researching subject twenty two teachings in c1ass-room activity and a aleatory patem seventy eight offour undreds pupils .In this methodology we aplly questionnaires that facilite to operate data face total of pupils and interviews made at school we register in recorder to permit an ample boarding. After analysis about quality and quantity data we observe the teachers ave convergent opinion about c1assification ,se1ective and exc1ude aspects of the e 'aluation but diverge at ideology aspects sensitiveness. Pupils agree ofien with the ethod evaluation we apply at the school and they show a litlle knowledge about the actual oarding apprendiceship evaluation.